IMPLEMENTASI PROYEK FOREST LAW ENFORCEMENT GOVERNANCE TRADE-VOLUNTARY PARTNERSHIP AGREEMENT (FLEGT-VPA) DI VIETNAM OLEH UNI EROPA - Annisa Andriani; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Illegal logging plays a role in the destruction of forests around the world and affects the people who live in them and rely on forest-generated resources. The European Union is one of the largest consumers of wood products in the world. As the biggest consumer, the EU has finally entered into an agreement with their wood supplying country with the FLEGT-VPA project which is expected to overcome illegal logging cases. This study uses a Pluralism perspective which focuses on the analysis of the International Organization level and the theory of international cooperation. Using the theory of international cooperation, this study aims to reveal the implementation of the Forest Law Enforcement Governance Trade-Voluntary Partnership Agreement (FLEGT-VPA) Project in Vietnam by the European Union. This study explains that the FLEGT-VPA project has strategic value obtained by the European Union and partner countries, for example in this case is Vietnam. The implementations carried out by the European Union in this project include Preparation of the VPA Implementation Structure, Development of a Legality Assurance System, Public Information Disclosure Mechanism, Independent Joint Evaluation of the Timber Legality Assurance System, FLEGT Licensed Timber Exports and European Union Border Control, and Monitoring the impact of this project. This implementation is still ongoing and can be said to be good, supported by regulations published by the Vietnamese government. Keywords: FLEGT-VPA, Implementation, European Union, Vietnam.